2018
DOI: 10.21926/obm.transplant.1802012
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Markers for Advantageous Perfusion in a Preclinical Donation after Cardiac Death Animal Model of Oxygenated Hypothermic Machine Perfusion (HOPE)

Abstract: Background: Extended criteria donors and donations after cardiac death provide organs that tend to be more sensitive to the stresses of preservation. The potential role of oxygen in preservation techniques remains to be clarified. The aim of this study was to compare

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…MicroRNAs are key post‐transcriptional regulators of gene expressions . They can bind to the 3′UTRs of the target mRNAs and repress mRNAs translation . CircRNAs generally exhibit regulatory functions on gene expression through acting as microRNA sponge .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs are key post‐transcriptional regulators of gene expressions . They can bind to the 3′UTRs of the target mRNAs and repress mRNAs translation . CircRNAs generally exhibit regulatory functions on gene expression through acting as microRNA sponge .…”
Section: Discussionmentioning
confidence: 99%
“…29 They can bind to the 3 0 UTRs of the target mRNAs and repress mRNAs translation. 29,30 CircRNAs generally exhibit regulatory functions on gene expression through acting as microRNA sponge. 15,31 miR-31 are reported to present pro-inflammatory or antiinflammatory activities under different condition.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…miRNAs are considered as the potential markers of advantageous perfusion [15]. Recent studies discovered that miR-29 is a key regulator in the pathophysiological process of fibrosis in kidney [16], lung [17], liver [18], as well as heart [19] through modulating collagen expression in these organs.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small (~ 22 nt) endogenous ncRNAs and involved in cell proliferation, survival, etc [12,13]. It has been reported that lncRNAs could interact with miRNA to regulate tumorigenesis and play key roles in the treatment and diagnosis for patients [14].…”
Section: Agingmentioning
confidence: 99%